Lipid anchoring of Arabidopsis phototropin 1 to assess the functional significance of receptor internalization: should I stay or should I go?. Issue 3 (3rd February 2015) - Preuten, Tobias; Blackwood, Lisa; Christie, John M.; Fankhauser, Christian
Summary The phototropin 1 (phot1) blue light receptor mediates a number of adaptive responses, including phototropism, that generally serve to optimize photosynthetic capacity. Phot1 is a plasma membrane‐associated protein, but upon irradiation, a fraction is internalized into the cytoplasm. Although this phenomenon has been reported for more than a decade, its biological significance remains elusive. Here, we use a genetic approach to revisit the prevalent hypotheses regarding the functional importance of receptor internalization. Transgenic plants expressing lipidated versions of phot1 that are permanently anchored to the plasma membrane were used to analyse the effect of internalization on receptor turnover, phototropism and other phot1‐mediated responses. Myristoylation and farnesylation effectively prevented phot1 internalization. Both modified photoreceptors were found to be fully functional in Arabidopsis, rescuing phototropism and all other phot1‐mediated responses tested. Light‐mediated phot1 turnover occurred as in the native receptor. Furthermore, our work does not provide any evidence of a role of phot1 internalization in the attenuation of receptor signalling during phototropism. Our results demonstrate that phot1 signalling is initiated at the plasma membrane. They furthermore indicate that release of phot1 into the cytosol is not linked to receptor turnover or desensitization.